Anatomical Analysis of Abdominal Aortic Aneurysms among Jordanian Patients Eligible for Treatment - Al-zoubi, Nabil; Yaghan, Rami; Swesi, Faisal; Elayyn, Rasheed (Jordan Medical Journal, 2018)
Introduction: There is no data regarding the anatomical characteristics of abdominal aortic aneurysms (AAAs) in Jordan. This study was conducted to evaluate the anatomical characteristics of AAAs in Jordanian patients who were eligible for treatment, and to compare the results to international published literature. Materials and Methods: From February 2014 to January 2017, a total of 80 multicenter computed tomography angiograms (CTAs) with 3-D reconstruction were reviewed for patients who had abdominal aortic aneurysms and were eligible for treatment by endovascular aortic repair (EVAR). Each CTA was analyzed for a set of 18 infrarenal aortoiliac anatomy measurements initially determined in each aneurysm. Results: The study population consisted of 80 patients in Jordan who underwent CTA sizing for EVAR eligibility. The patients were primarily men (92.5%) with an average age of 70.75 years, while female patients represented 7.5% with an average age of 75.50 years. The average maximum aneurysm diameter was 65.36 mm, average proximal neck diameter was 23.43 mm, and average proximal neck length was 25.68 mm. The average diameters of the right and left external iliac arteries were 10.07 mm and 10.02 mm, respectively. Conclusion: Among the 18 anatomical characteristics studied, the maximum AAA size in Jordanian patients was large in comparison to that of the published data. Moreover, Jordanian patients were older at time of diagnosis. This could be explained by the fact that there is an absence of a national screening program for AAA in Jordan that would allow early diagnosis and treatment of abdominal aortic aneurysms of smaller sizes.